Fitrah-Based Islamic Education: A Study of The Concept of Fitrah-Based Education by Harry Santosa - Nuranisa, Lya; Anwar, Saepul; Firmansyah, Mokh. Iman (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to examine the design of Islamic education based on human fitrah through an analysis of the Fitrah Education concept by Harry Santosa. This research was conducted using a literature review method, which involved collecting data from various sources such as books, journals, and other literature. The collected data was then analyzed through several stages, including abstraction, interpretation, and conclusion. The findings indicate that the design of Islamic education based on fitrah, as developed by Harry Santosa, involves several key components. First, educational objectives must align with the mission of human creation. Second, the development of students' characteristics is carried out based on eight dimensions of fitrah. Third, the learning method utilizes an operational framework table. Fourth, the implementation of a reflection journal serves as an evaluation system. Theoretically, these findings enrich the study of Islamic education by providing a more holistic perspective on understanding students' fitrah potential. Educational institutions can adapt this concept into their curriculum and learning strategies to create an educational environment that better suits students' natural needs. This approach is expected to shape individuals who are not only knowledgeable but also aware of their role and responsibilities as caliphs on earth.